Exploring the implementation of the TIME Home Learning programme and learning trajectories of 5- to 7-year-olds The TIME programme in its ecosystem: What does it take for a school to commit to TIME? - von Blottnitz, Magali (Wordworks, 2024)
This is the third in a series of learning briefs that explore the implementation of the TIME Home Learning programme and learning trajectories of 5- to 7-year-olds. This brief is based on interviews held in 2022 with stakeholders from Western Cape schools. It focuses on schools’ commitment to TIME, a programme that is offered on a sign-up and co-payment basis. The brief unpacks the factors influencing schools’ decision to either register for the programme, or turn it down, including strategic priorities, past experiences and financial constraints. As such, the brief offers interesting insights for NGOs about opportunities and pitfalls of co-payment models.
TIME Learning Brief No 3
More information about the TIME (Together in My Education) home-learning programme and materials can be found in open access at: https://wwhomeliteracy.org.za/time/
Keywords: Early learning; Early literacy; South Africa; Wordworks; Home-learning; Parental involvement; Grade R; Grade 1; School management; Co-payment models